Tomato leaves methanol extract posses anti-inflammatory activity via inhibition of Lipopolysacharide (LPS)-induced Prostaglandin (PGE2) - Semail, Sulawati; Amid, Azura; Jamal, Parveen (2011)
Recently, the leaves of tomato plant that contained several active compound including alkaloid, steroid and flavanoid has been used for treatment of variety of diseases included anticancer, anti-oxidant and anti-gout. Although a number of pharmacological properties have already been demonstrated, the anti-inflammatory effect of tomato leaves action and its associated molecular mechanisms have not yet been fully investigated. In this study, in order to observe the antiinflammatory action of Solanum lycopersicum extract on lipopolysaccharide (LPS)-stimulated macrophages, its inhibitory of inflammation activity was investigated by observing the Prostaglandin E2 (PGE2 ) production using PGE2 enzyme immunometric assay kit (Cayman CO., Ann Arbor, MI, USA). Results showed that the tomato leaves extract inhibited the productions of inflammatory mediators (PGE2 ) which plays a central role in the anti-inflammatory activity. At the highest concentration (100µg/ml) of tomato leaves extract tested, the PGE2 production was reduced 37.41% compared to the untreated. The COX-2 gene expression also reduced following increment in the extract concentration. Hence, these present study may support that the leaves of Solanum lycopersicum extract potentially use in treatment of inflammatory related disease through the inhibition of PGE2 releases.